Solvothermally Synthesized Hierarchical Aggregates of Anatase TiO2 Nanoribbons/Nanosheets and Their Photocatalytic–Photocurrent Activities - Kadhim Al-Attafi; Hamza A. Mezher; Ali Faraj Hammadi; Amar Al-Keisy; Sameh Hamzawy; Hamzeh Qutaish; Jung Ho Kim (Nanomaterials, 2023)
Hierarchical aggregates of anatase TiO2 nanoribbons/nanosheets (TiO2-NR) and anatase TiO2 nanoparticles (TiO2-NP) were produced through a one-step solvothermal reaction using acetic acid or ethanol and titanium isopropoxide as solvothermal reaction systems. The crystalline structure, crystalline phase, and morphologies of synthesized materials were characterized using several techniques. According to our findings, both TiO2-NR and TiO2-NP were found to have polycrystalline structures, with pure anatase phases. TiO2-NR has a three-dimensional hierarchical structure made up of aggregates of TiO2 nanoribbons/nanosheets, while TiO2-NP has a nanoparticulate structure. The photocatalytic and photocurrent activities for TiO2-NR and TiO2-NP were investigated and compared with the widely used commercial TiO2 (P25), which consists of anatase/rutile TiO2 nanoparticles, as a reference material. Our findings showed that TiO2-NR has higher photocatalytic and photocurrent performance than TiO2-NP, which are both, in turn, higher than those of P25. Our developed solvothermal method was shown to produce a pure anatase TiO2 phase for both synthesized structures, without using any surfactants or any other assisted templates. This developed solvothermal approach, and its anatase TiO2 nanostructure output, has promising potential for a wide range of energy harvesting applications, such as water pollution treatment and solar cells.